2020
DOI: 10.1021/acsnano.0c05250
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Oxidation Studies of High-Entropy Alloy Nanoparticles

Abstract: Although high-entropy alloys (HEAs) have shown tremendous potential for elevated temperature, anticorrosion, and catalysis applications, little is known on how HEA materials behave under complex service environments. Herein, we studied the high-temperature oxidation behavior of Fe0.28Co0.21Ni0.20Cu0.08Pt0.23HEA nanoparticles (NPs) in an atmospheric pressure dry air environment by in situ gas-cell transmission electron microscopy. It is found that the oxidation of HEA NPs is governed by Kirkendall effects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 78 publications
2
72
0
Order By: Relevance
“…Contrary to the reducing conditions in ORR, the high positive potentials required for OER tend to oxidize the surface of the metal catalysts and form metal oxides or (oxy)hydroxides ( 87 ). Recent studies have revealed that oxidation of HEAs is governed by the Kirkendall effects ( 88 ), where the metal atoms diffuse outward and form disordered oxidation layers. It is thereby important to note that in most cases, the active sites of the HEA catalysts for OER are the restructured oxide or (oxy)hydroxide surface layers instead of the original metallic phase.…”
Section: Heas For Catalysismentioning
confidence: 99%
“…Contrary to the reducing conditions in ORR, the high positive potentials required for OER tend to oxidize the surface of the metal catalysts and form metal oxides or (oxy)hydroxides ( 87 ). Recent studies have revealed that oxidation of HEAs is governed by the Kirkendall effects ( 88 ), where the metal atoms diffuse outward and form disordered oxidation layers. It is thereby important to note that in most cases, the active sites of the HEA catalysts for OER are the restructured oxide or (oxy)hydroxide surface layers instead of the original metallic phase.…”
Section: Heas For Catalysismentioning
confidence: 99%
“…Hybrid Monte Carlo and molecular dynamics calculations using first-principles density functional theory 46 were also in agreement that hydrogen interactions with the surface do not induce any surface segregation phenomenon (Figure S1c) in contrast to the case of oxygen. 31 Then, a two-step process is conducted (Figure S2): the HEA NPs were first oxidized in atmospheric air (red box) and then reduced in H 2 environment (gray box). The individual HEA NP at the bottom left and the three HEA NPs at the top are magnified and displayed separately in Figure 2a,b.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The authors recently reported the oxidation of HEA NPs under dried air at 400 °C and showed that Kirkendall effect governed the logarithmic behavior of the oxide layer growth kinetics. 31 Here, we used in situ closed-cell atmospheric pressure transmission electron microscopy 32−44 to study the high-temperature reduction behavior of oxidized FeCoNiCuPt HEA NPs in H 2 environment. In our study, closed-gas cell design [37][38][39][40][41][42][43]45 based on microfabricated devices was used to expose the NPs to atmospheric pressure H 2 at 400 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2 Various unique synergistic effects result from such mixtures, including high con guration entropy, lattice distortion, sluggish diffusion and cocktail effects, and endow HEAs with high mechanical strength, good thermal stability and superior corrosion resistance. [3][4][5] To date, several synthetic strategies have been reported, such as bulk melting, 6 solid state processing 7 and additive manufacturing, 8,9 all of which have principally focused on the fabrication of bulk HEAs. However, the development of HEA nanoparticles (NPs) with a mean diameter of less than 10 nm lags signi cantly behind, despite the potential practical applications of these NPs in catalysis, nanoelectronics and material science owing to their large surface area-tovolume ratio and nanoscale size effect.…”
Section: Introductionmentioning
confidence: 99%